2016
DOI: 10.1111/crj.12486
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audiovisual distraction on the tolerability of flexible bronchoscopy: a randomized trial

Abstract: Our findings showed that audiovisual distraction had a positive effect on the tolerability of FB. This method has important potential as a simple and practical approach in reducing discomfort during invasive diagnostic and treatment procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have also confirmed that the higher the patient’s satisfaction after bronchoscopy, the higher their willingness to undergo the examination again 7. Many studies have sought to improve patients’ satisfaction by improving perioperative nursing,8 the operating room environment, shortening the waiting time9 and using music therapy 10. However, these methods only affected the patients on a psychological level, and the physiological discomfort in the perioperative period was the main reason for the low acceptance and low satisfaction of the diagnosis and treatment technique.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have also confirmed that the higher the patient’s satisfaction after bronchoscopy, the higher their willingness to undergo the examination again 7. Many studies have sought to improve patients’ satisfaction by improving perioperative nursing,8 the operating room environment, shortening the waiting time9 and using music therapy 10. However, these methods only affected the patients on a psychological level, and the physiological discomfort in the perioperative period was the main reason for the low acceptance and low satisfaction of the diagnosis and treatment technique.…”
Section: Discussionmentioning
confidence: 96%
“…14,17 Distraction is a non-pharmacological intervention technique, which can divert a patient's attention away from noxious or unpleasant stimuli, and is applied in clinical practice to reduce pain, anxiety, and fear associated with painful medical procedures. [18][19][20] The ideal distractor should possess multiple sensory modalities such as visual, auditory and kinesthetic, and active emotional involvement. These various abilities can hold the full attention of a child so as to minimize dental anxiety.…”
mentioning
confidence: 99%
“…Navidian study and other studies did not report any significant change in anxiety levels by listening to music. [ 11 26 27 ] Gupta concluded that music did not decrease pain, anxiety, or unfavorable behaviors significantly. [ 28 ] The heterogeneity in audio and audiovisual distraction results may be due to the different forms and types of equipment used, different types of content played, and the volume.…”
Section: Discussionmentioning
confidence: 99%
“…This technique results in the involvement of the patient's attention, the distraction of the patients' vision from the dental treatment field, resulting in a comforting dental experience. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%